Application of a Cloud Video Conference Method for Recruiting Healthy Subjects Into an Early-Phase Clinical Trial During the COVID-19 Pandemic - Wang, Zejuan; Du, Aihua; Li, Min; Zang, Siqi; Liu, Xiaona; Zhang, Dan; Chen, Gang; Zhang, Lina; Zhang, Yanan; Wang, Jin (Frontiers in Public Health, 2021)
Objective: To explore the effect of applying cloud-video methods in informed consent process in early clinical trials under COVID-19 epidemic. Methods: All participants who intend to participate in one trial project were informed by cloud video conference before signing the informed consent forms (ICF). Among those who visited to sign the ICF onsite were evaluated the satisfaction with the methods and the understanding of the trial ICF by questionnaire. Results: 165 subjects participated in cloud-video informed explanation and 142 signed and dated on ICFs. The survey showed that 100% of the subjects accepted the video informed process with very good or good evaluation and gave the right response of some questions about the trial. 136 (95.8%) subjects believed that the effect of video informed process was consistent with the onsite situation. 139 (97.9%) subjects expressed their willingness to participate in online video informed consent. Conclusions:Video informed process could achieve the same effect as on-site way. This method greatly saved the time and cost of transportation for the subject with good acceptance; especially under the COVID-19 epidemic, it is conducive to reduce the risk of subject infection in the travel, and avoid the crowdness on site .